Maturity Level on the Quality of Pineapple (Ananas comosus L Merr.) Smooth Cayenne Variety During Storage Period - Fawaz Fauzan; Dodi Budirokhman (Agricultural Science, 2025)
harvest can produce good quality fruit. The characteristics of fruit commodities at various levels of maturity at harvest time greatly determine the quality because different levels of fruit maturity will affect the quality of the fruit, and inappropriate levels of maturity will cause low fruit quality. This research was carried out by the UGJ Cirebon Faculty of Agriculture Laboratory from July to August 2024. This research used an experimental method with a Completely Randomized Design (CRD). Variables measured included weight loss, total dissolved solids content and vitamin C. Tests were carried out using analysis of variance and Duncan's test. The results showed that differences in pineapple ripeness levels made a difference to fresh weight, weight loss and total soluble solids levels. High fresh fruit weight and weight loss were obtained at a maturity level of 20%, while high total soluble solids were obtained at a maturity level of 30%. Vitamin C levels showed no differences at various stages of maturity.